2022
DOI: 10.3390/microorganisms10112100
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Biochemical Characterization of Bifidobacterium pseudocatenulatum JCLA3 Isolated from Human Intestine

Abstract: Bifidobacteria have been investigated due to their mutualistic microbe–host interaction with humans throughout their life. This work aims to make a biochemical and genomic characterization of Bifidobacterium pseudocatenulatum JCLA3. By multilocus analysis, the species of B. pseudocatenulatum JCLA3 was established as pseudocatenulatum. It contains one circular genome of 2,369,863 bp with G + C content of 56.6%, no plasmids, 1937 CDSs, 54 tRNAs, 16 rRNAs, 1 tmRNA, 1 CRISPR region, and 401 operons predicted, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…However, it has been suggested that B. dentium possesses the ability to remove terminal fucose from HMOs [ 48 ]. Researchers found a smaller number of glycosyl hydrolase genes in the genomes of Bifidobacterium angulatum JCM 7096(T) and Bifidobacterium pseudocatenulatum JCLA3 [ 49 , 50 ]. The B. thermophilum genome contains a β-galactosidase gene, a finding that hints at its potential to degrade HMOs since β-galactosidase can participate in their metabolism; however, the exact mechanism remains uncharted [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been suggested that B. dentium possesses the ability to remove terminal fucose from HMOs [ 48 ]. Researchers found a smaller number of glycosyl hydrolase genes in the genomes of Bifidobacterium angulatum JCM 7096(T) and Bifidobacterium pseudocatenulatum JCLA3 [ 49 , 50 ]. The B. thermophilum genome contains a β-galactosidase gene, a finding that hints at its potential to degrade HMOs since β-galactosidase can participate in their metabolism; however, the exact mechanism remains uncharted [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of constitutive genes in different strains of B. longum strains was made: tlyC , cbh , glnE , pNPOx , ahpC , trxA , trxB [ 11 , 17 , 18 ]. The MLSA approach has been used to generate a robust and highly discriminatory supertree to infer phylogeny in the genus Bifidobacterium .…”
Section: Methodsmentioning
confidence: 99%
“…The MLSA approach has been used to generate a robust and highly discriminatory supertree to infer phylogeny in the genus Bifidobacterium . MLSA was performed according to González–Vázquez et al, 2022 [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations